Depressive symptoms, mental wellbeing, and substance use among adolescents before and during the COVID-19 pandemic in Iceland: a longitudinal, population-based study ... - Thorisdottir, Ingibjorg E.; Asgeirsdottir, Bryndis Bjork; Kristjansson, Alfgeir L.; Valdimarsdottir, Heiddis; Jonsdottir Tolgyes, Erla Maria; Sigfusson, Jon; Allegrante, John P.; Sigfusdottir, Inga Dora; Halldorsdottir, Thorhildur (Columbia University, 2021)
Background: Adolescence represents a crucial developmental period in shaping mental health trajectories. In this study, we investigated the effect of the COVID-19 pandemic on mental health and substance use during this sensitive developmental stage. Methods: In this longitudinal, population-based study, surveys were administered to a nationwide sample of 13-18-year-olds in Iceland in October or February in 2016 and 2018, and in October, 2020 (during the COVID-19 pandemic). The surveys assessed depressive symptoms with the Symptom Checklist-90, mental wellbeing with the Short Warwick Edinburgh Mental Wellbeing Scale, and the frequency of cigarette smoking, e-cigarette use, and alcohol intoxication. Demographic data were collected, which included language spoken at home although not ethnicity data. We used mixed effects models to study the effect of gender, age, and survey year on trends in mental health outcomes. Findings: 59 701 survey responses were included; response rates ranged from 63% to 86%. An ...